A Pancasila as a Critique of Legal Positivism in National Lawmaking - Ni Putu Ega Maha Wiryanthi; Putu Wahyu Widiartana; Dominikus Rato; Fendi Setyawan (Jurnal Smart Hukum (JSH), 2026)
Legal positivism has contributed to legal certainty in Indonesia, but its dominance in national lawmaking may reduce law to formal legality and procedural validity. This article examines Pancasila as a philosophical critique of legal positivism in the formation of national law. The study employs normative legal research, drawing on philosophical, conceptual, and statutory approaches. The analysis shows that Pancasila should not be treated merely as an ideological symbol or a formal source of legal validity. Rather, it functions as a substantive evaluative standard for testing whether legislation reflects human dignity, democratic participation, social justice, national unity, and moral responsibility. The novelty of this article lies in treating Pancasila not only as the source of all sources of law, but also as a critical framework for correcting legal formalism in legislative practice. In the future, national lawmaking needs to balance legal certainty with substantive justice so that positive law remains rooted in the philosophical ideals of Pancasila.